Time-Experience and the Limits of Objectification: Remarks on the Phenomenological Implications of Hermann Weyl’s Treatment of the Intuitive Continuum - Giulio Marchegiani (Philosophia Scientiæ)
The paper focuses on providing a mathematical expression for the intuitive continuum of space and time, tracing some significant stages of Hermann Weyl’s thinking on the subject from the standpoint of its relations to Husserl’s phenomenology. While Weyl and Husserl both recognise the irreducibility of a subjective point of reference, their agreement in recognising the central role of intuitive experience is also striking. The failure of Weyl’s attempt in Das Kontinuum (1918) to provide a mathematical formulation for the intuitive continuum, due to the recognition of a radical heterogeneity between the fluid character of the latter and the mathematical continuum, is taken into account. In the subsequent intuitionistic-Brouwerian period, however, Weyl develops a formal scheme based on the part-whole relation that is capable of capturing the dynamic character of the intuitive continuum, in which individual elements become simple boundaries. In this context, the relations between Weyl’s conception of the continuum and Husserlian analyses of time are discussed.